Comparison of the lysis-centrifugation and agitated biphasic blood culture systems for detection of fungemia. - Murray, P R (1991)
Although the detection of fungemia has been improved by the use of vented or biphasic blood culture bottles, the best recovery and earliest detection have been reported in the Isolator lysis-centrifugation system. It was recently demonstrated that improved detection of both bacteria and fungi was accomplished by mechanically agitating blood culture bottles for the first 24 h of incubation. In this study the detection of fungemia by use of the Isolator system was compared with that of an agitated biphasic system. A total of 182 fungi were isolated from blood specimens inoculated into both culture systems. No difference in the overall recovery of fungi or individual species of yeasts was observed between the two systems. However, all seven isolates of Histoplasma capsulatum were recovered in the Isolator system only. The time required to detect fungemia with each of the two systems was also compared. No statistically significant difference was observed. From the data collected during this 18-month study, it can be concluded that the overall recovery and time of detection of yeasts are equivalent in the lysis-centrifugation system and the agitated biphasic blood culture system. The lysis-centrifugation system is still superior for the detection of filamentous fungi such as H. capsulatum.